Raising the Quality of Extension Reporting: An Evaluation Leadership Team Model - Colleen Gariton; Alexa Lamm; Glenn Israel; David Diehl (EDIS)
This new 5-page article reviews the Evaluation Leadership Team (ELT) model. This article provides more detail about the model, possible ways to implement this model in the Extension system, and potential impacts of implementing this model. If this model is implemented, it could help streamline and standardize evaluation in Extension through the creation of more standardized evaluations and templates by ELT members within priority groups. This could have huge ramifications for Extension across the country. With standardization, they will be able to better assess their impact and the programming provided, as well as to prove their worth to their stakeholders and the public. Written by Colleen Gariton, Alexa Lamm, Glenn Israel, and David Diehl and published by the UF/IFAS Department of Agricultural Education and Communication.